Aerosol gene delivery using viral vectors and cationic carriers for in vivo lung cancer therapy. (June 2014) - Hong, Seong-Ho; Park, Sung-Jin; Lee, Somin; Cho, Chong Su; Cho, Myung-Haing
<x xml:space="preserve">Abstract</x> Introduction: Lung cancer has the highest mortality rate among all cancers in both men and women. Aerosol delivery is a noninvasive method for gene delivery to the lungs, although efficient and biocompatible vectors need to be developed for lung cancer therapy. Areas covered: This review summarizes recent advances in airway gene delivery for lung cancer treatment in animal models using viral vectors or cationic polymers. Viral vectors including lentiviruses and adenoviruses have been used for airway gene delivery because of their high transfection efficiency. Cationic polymers have also been developed for aerosol gene therapy owing to their biocompatibility and ease of modification. Expert opinion: Efficient delivery and specific promoters are needed for lung cancer therapy. Capsid engineering or PEGylation can lower immunogenicity. Moreover, immunotherapy and oncolytic viruses need to be tested with aerosol delivery for lung cancer therapy. Meanwhile, naturally existing cationic materials may allow the development of novel and biocompatible carriers. In combination with various technologies for aerosol delivery, novel and specific carriers could be developed for lung cancer therapy in the future. Finally, standardized protocols for quantifying and manufacturing viral vectors and cationic polymers need to be developed in order to ensure biosafety.